Isolation and characterization of bacteriophage from squid (Loligo vulgaris) - Agusalim, Farah Hanim (2015)
This project was carried out to isolate and characterize the bacteriophage against pathogenic bacteria from squid (Loligo vulgaris). Commonly, squid easily contaminated with pathogen that may lead to food-borne diseases. Hence phage therapy can be applied by using specific baceteriophage against susceptible pathogenic bacteria cells. Six bacteria were isolated from the squid and labelled as bacteria A, B, C, D, E and F. All isolated bacteria were subjected to morphology observation using Gram staining. Based on the Gram staining observation, bacteria A and E shows Gram positive with cocci and rod shape while bacteria B, C, D and F shows Gram negative with rod shape. All these bacteria including another two species of known bacteria which are Pseudomonas aeruginosa and Escherichia coli were used as the host for bacteriophage isolation. Among the bacteria, only C, D, E and Pseudomonas aeruginosa were infected by bacteriophage. The purified bacteriophages were labelled as ØF1, ØF2, ØH2 and ØS. Then isolated bacteriophages were characterized based on their genomic, biology and physical characteristics. All four phages nucleic acid was presumptively identified as DNA with same digestion profile pattern for Eco RІ and Hind ІІІ. ØF1 and ØS display the same protein profile with major protein size of 35 kDa, ØH2 was approximately 35 kDa, and ØF2 exhibit the largest protein band size with molecular mass of 45 kDa. All four phages displayed to be heat stable at temperatures 4°C, 25°C and 37°C which demonstrated a wide spectrum of pH tolerance from pH 4 to 8.